Deskripsi Pelaksanaan Projek Penguatan Profil Pelajar Pancasila Dengan Tema Kewirausahaan Pada Materi Aritmatika Sosial - Djam'an, Nurwati; Sarmita, Sarmita; Alimuddin, Alimuddin (Universitas Dr. Soetomo, 2025)
Abstract The rapid advancement of technology, the ever-evolving social and cultural dynamics, environmental transformations, and the differing characteristics of the future job market have significantly impacted education at all levels and across all aspects of culture. These factors have served as the driving force behind the emergence of the Pancasila Student Profile, which is one of the key implementations of the Merdeka Curriculum. This descriptive qualitative research study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) under the theme of entrepreneurship, integrated with social arithmetic material. The researcher employed purposive sampling to determine the research subjects: three educators and six students. Data was collected through student activity observations, P5 implementation interview guidelines, and social arithmetic tests. The data were analyzed using an interactive qualitative analysis model involving the stages of data condensation, data display, and conclusion drawing or verification. The findings reveal that the P5 design process includes planning time allocation and dimensions, identifying school readiness, selecting a general theme, determining specific topics, designing project modules, selecting dimensions, elements, and sub-elements, and exploring the project flow. The implementation demonstrated strong integration between school readiness, project execution, and structured evaluation. Despite some challenges, such as student discipline issues and limited supervision, the project improved students' understanding of the subject matter. It supported the development of key Pancasila Student Profile dimensions, namely critical thinking, creativity, and collaboration. Furthermore, the results of the social arithmetic tests indicate that the P5 implementation contributed to improving students' conceptual understanding. Keywords: Entrepreneurship; Independent Curriculum; Pancasila Student Profile Strengthening Project; Social Arithmetic. Abstrak Perkembangan teknologi yang sangat cepat, dinamika sosial dan budaya yang terus berubah, transformasi lingkungan hidup, serta perbedaan karakteristik dunia kerja di masa depan memberikan dampak yang signifikan terhadap pendidikan di semua jenjang dan pada setiap aspek kebudayaan merupakan hal yang melatarbelakangi munculnya Profil Pelajar Pancasila yang merupakan salah satu bentuk Implementasi Kurikulum Merdeka. Penelitian ini merupakan penelitian kualitatif deskripstif bertujuan untuk mengetahui pelaksanaan Projek Penguatan Profil Pelajar Pancasila (P5) dengan tema kewirausahaan pada materi aritmatika sosial. Peneliti menggunakan Teknik purposive sampling dalam penentuan subjek penelitian yang terdiri dari 3 subjek dari pendidik dan 6 siswa. Data diperoleh dari hasil observasi aktivitas siswa, pedoman wawancara keterlaksanaan P5, dan tes aritmatika sosial. Data dianalisis menggunakan analisis kualitatif model interaktif dengan tahapan: kondensasi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa proses desain P5 terdiri atas merancang alokasi waktu dan dimensi, mengidentifikasi kesiapan sekolah, memilih tema umum, penentuan topik spesifik, merancang modul projek, pemilihan dimensi, elemen dan sub-elemen, dan mengeksplorasi alur projek. Keterlaksanaan menunjukkan integrasi yang baik antara kesiapan sekolah, pelaksanaan projek, dan evaluasi terstruktur. Meskipun terdapat kendala seperti ketidaktertiban siswa dan kurangnya kontrol, projek ini efektif dalam membantu pemahaman materi dan mendukung tercapainya dimensi bernalar kritis, kreatif, dan bergotong royong. Kemudian, hasil tes aritmatika sosial, terlihat bahwa pelaksanaan P5 dapat meningkatkan pemahaman konsep siswa. Kata Kunci: Aritmatika Sosial; Kewirausahaan; Kurikulum Merdeka; Projek Penguatan Profil Pelajar Pancasila